Research on Electric Vehicle’s Charger Based on PWM Rectifier - LUO Yunfei (Kongzhi Yu Xinxi Jishu)
A charging-discharging device of electric vehicle’s battery is designed based on main circuit topology of three-phase voltage source PWM rectifier. The system structure of the device and control strategy of PWM rectifier are mainly analyzed and researched. The experiment results indicate that the charger has some advantages such as better dynamic and static performance, sinusoidal grid-current waveform, high input power factor, and bidirectional transformation of energy.